Hemoplasmose em felídeos silvestres de vida livre e cativeiro no estado do Mato Grosso, Brasil - Pitchenin, Letícia Camara (2019)
Hemoplasms are erythrocyte parasites characterized by being always in the epidermocytic position and causing anemia in infected animals. In felines, three species of Mycoplasmas are described: Mhf, CMhm and CMt. Considered important reservoirs of disease, wild felids can play a crucial role in the epidemiology of hemoglobin. Therefore, the objective of this study was to detect the occurrence of these three species of hemoplasms of clinical importance in wild felines of free life and captivity. Blood samples of 23 wild felids from 6 different species (Leopardus colocolo, Leopardus pardalis, Leopardus wiedii, Panther onca, Puma concolor and Puma yagouaorundii) were collected, extracted and submitted to polymerase chain reaction (PCR) in the period of August 2014 and August 2018. There was no detection of Mhf in the felids of this study. CMhm was detected in 3 animals (12.5%), two of free life and one of captivity, being these belonging to the same species (Leopardus pardalis). CMt was present in 12 felids (52.2%), 6 free life animals and 6 captive animals. All species of wild felids tested had at least one positive animal for this microorganism, with CMhm and CMt coinfection. This is the first report of the occurrence of CMt in Leopardus colocolo, Leopardus wiedii, Puma concolor, Panthera onca and Puma yagouaroundi. The mechanisms of transmission are still uncertain for these microorganisms. The study of wild feline populations may contribute actively to understanding the epidemiology of hemoplasmosis and the importance of these animals as reservoirs and could significantly affect human health and domestic and wild populations.